How Does Canva Application Effect Students’ Writing Skills on Narrative Text for The Tenth Grade of SMAN 1 Kesamben - Fathimatun Nida’ Asalami; Hesty Puspita Sari; Winarsih Winarsih (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This research aims to find out the effectiveness of the Canva application in improving students' writing skills in narrative texts in class X-A with a total of 30 students at Sman 1 Kesamben. The design of this research is Pre Experimental using One Group Pretest-Posttest. In One Group Pretest-Posttest there are 3 steps, first the researcher gives a pre-test, then carries out treatment, and after treatment the researcher gives a post-test. To obtain data the author used a test, before the test was tested on students, a trial test was carried out at the same level to determine the reliability and validity of the test. Data analysis techniques use SPSS version 23. The results of this study show that the average pre-test score is 69 and the average post-test score is 82, this shows that the post-test score and average are better than the pre-test. Apart from that, the t-test result showed that the score was sig. (2-tailed) <0.05 means there is a difference between the scores from the pretest and posttest. This means that the hypothesis will not be rejected and the alternative hypothesis will be accepted, which can be interpreted as meaning that there is a significant influence of using Canva on the writing skills of class X-A students at SMAN 1 Kesamben. Based on the results of this research, it is recommended for teachers to use the Canva application in learning English, especially writing skills so that students can learn easily and have fun. Apart from that, it is recommended for future researchers to research the use of the Canva application in learning with other topics to find out students' or teachers' responses to using the Canva application.